A Fully Self-Healing Piezoelectric Nanogenerator for Self-Powered Pressure Sensing Electronic Skin - Maosen Yang; Jinmei Liu; Dong Liu; Jingyi Jiao; Nuanyang Cui; Shuhai Liu; Qi Xu; Long Gu; Yong Qin (Research, 2021)
As an important way of converting mechanical energy into electric energy, a piezoelectric nanogenerator (PENG) has been widely applied in energy harvesting as well as self-powered sensors in recent years. However, its robustness and durability are still severely challenged by frequent and inevitable mechanical impacts in real application environments. Herein, a fully self-healing PENG (FS-PENG) as a self-powered pressure sensing electronic skin is reported. The self-healing piezoelectric composite and self-healing Ag NW electrode fabricated through mixing piezoelectric PZT particles and conductive Ag NWs into self-healing polydimethylsiloxane (H-PDMS) are assembled into the sandwich structure FS-PENG. The FS-PENG could not only effectively convert external stimulation into electrical signals with a linear response to the pressure but also retain the excellent self-healing and stable sensing property after multiple cycles of cutting and self-healing process. Moreover, a self-healing pressure sensor array composed of 9 FS-PENGs was attached on the back of the human hand to mimic the human skin, and accurate monitoring of the spatial position distribution and magnitude of the pressure was successfully realized.